Apel y la hermenéutica filosófica de Gadamer - Scivoletto, Gonzalo (2018)
“Apel and Gadamer’s Philosophical Hermeneutics”. This paper seeks to reconstruct the core of Apel’s criticism of Gadamer’s philosophical hermeneutics. In order to achieve this, three texts post-Transformation of Philosophy by Apel are analyzed. All of them go beyond the debate between hermeneutics and critique of ideology. Throughout the paper I will attempt to demonstrate that the concepts introduced by Apel offer the possibility of an enlightened or critical normative hermeneutics.